PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI BERPRESTASI, DAN KOMPENSASI TERHADAP KEDISIPLINAN GURU DI PERGURUAN TAMANSISWA CABANG JETIS YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims to find out the significant influence of headmaster’s leadership, achievement motivation and compensation toward teachers’ discipline in Perguruan Tamansiswa Cabang Jetis.The participants of this research involved 125 teachers who are teaching in Perguruan Tamansiswa Cabang Jetis. From 125 questionnaires were given, only 111 of those were submitted by the participants. The questionnaires contain 88 item statements and it was collected by total sampling technique. To analyze the data, the researcher used quantitative approach with static descriptive technique. Correlation analysis, simple regression and double regression are also used in analyzing the data.The result of descriptive analysis shows that principal leadership, achievement motivation and compensation had significant influence toward teacher discipline. It was also proven by teachers’ discipline, principal leadership, achievement motivation, and compensation are in the high categories. The result of data analysis also showed that principal leadership had positive and significant influence to the teachers’ discipline.